Effect of Female Population, Urbanization and Trade Openness on Carbon Dioxide Emissions - KWAKWA, Paul; OPOKU-MARFO, Emmanuel; ANSU-MENSAH, Peter; ABOAGYE, Solomon (International Journal of Environmental, Sustainability, and Social Science, 2024)
The agenda to reduce carbon dioxide emissions in order to mitigate climate change remains a global concern. Researchers, policymakers and governments have shown interest in this regard. While empirical studies on the subject matter has been increasing conflicting results and little evidence on the effects of some variables necessitate for further studies. In this study the effect of female population, urbanization and trade openness on carbon dioxide emission in Ghana is assessed. The study used the Stochastic Impacts by Regression on Population, Affluence, & Technology (STIRPAT) model as the foundation for empirical modelling. Time series data spanning from 1971-2018 was used for regression analysis. In both long run and short run periods, urbanization was noted to exert positive influence on carbon dioxide emission while trade openness and female population exert negative effect on carbon dioxide emission. Thus, growth in urbanization increases carbon dioxide emission while the opposite is the case for trade openness and female population. Findings from the study suggest intensifying the empowerment of women could be a crucial catalyst for the achievement of Ghana’s nationally determined contributions toward CO2 reduction. Also, trade negotiations that promote environmental protection should not be relaxed